Revisiting Schistosoma mansoni Micro-Exon Gene (MEG) Protein Family: A Tour into Conserved Motifs and Annotation - Nedvědová, Štěpánka; De Stefano, Davide; Walker, Olivier; Hologne, Maggy; Miele, Adriana Erica (Biomolecules, 2023)
Genome sequencing of the human parasite Schistosoma mansoni revealed an interesting gene superfamily, called micro-exon gene (meg), that encodes secreted MEG proteins. The genes are composed of short exons (3-81 base pairs) regularly interspersed with long introns (up to 5 kbp). This article recollects 35 S. mansoni specific meg genes that are distributed over 7 autosomes and one pair of sex chromosomes and that code for at least 87 verified MEG proteins. We used various bioinformatics tools to produce an optimal alignment and propose a phylogenetic analysis. This work highlighted intriguing conserved patterns/motifs in the sequences of the highly variable MEG proteins. Based on the analyses, we were able to classify the verified MEG proteins into two subfamilies and to hypothesize their duplication and colonization of all the chromosomes. Together with motif identification, we also proposed to revisit MEGs' common names and annotation in order to avoid duplication, to help the reproducibility of research results and to avoid possible misunderstandings.
Keywords: reprodukovatelnost výsledků; gene annotation; phylogeny; exony; mapování chromozomů; Animals; Humans; Exons; Schistosoma mansoni; lidé; Phylogeny; Reproducibility of Results; zvířata; fylogeneze; Chromosome Mapping; micro-exon genes (MEG)